PENGUKURAN AIRBAND FREKUENSI MENGGUNAKAN SOFTWARE DEFINED RADIO - Bambang Bagus Harianto; Achmad Setyo Prabowo; Mochammad Rifa'i; Totok Warsito (Politeknik Penerbangan Surabaya, 2019)
Aviation communication is a vital object in the world of aviation, this is indicated by the existence of regulations listed in Ministerial Regulation (PM) Number 55 of 2016. In the world of aviation communication is carried out between air traffic controllers (ATC) and the development of the digital world at this time is very rapid so that make researchers can use it as research material. This study aims to create an innovation that utilizes digital technology using a software called GQRX, GNU Radio and Virtual Radar which will be validated using a web observing flight. This study uses a frequency of 125,094 MHz which is the approach frequency of Juanda Airport in Surabaya. This assessment uses 2 personal computers, 1 raspberry pi which is supported using 3 RTL-SDR.